Neither star wars nor santuary constraining the military uses of space - O'Hanlon, Michael E. (Brookings Institution Press, 2004)
Space has been militarized for over four decades. Should it now be weaponized? This incisive and insightful book argues that it should not. Since the cold war, space has come to harbor many tools of the tactical warfighter. Satellites have long been used to provide strategic communication, early warning of missile launch, and arms control verification. The U.S. armed forces increasingly use space assets to locate and strike targets on the battlefield. To date, though, no country deploys destructive weapons in space, for use against space or Earth targets, and no country possesses ground-based.